The Influence of School Financing Management, School Climate, and Teacher Performance on School Quality in Public Junior High Schools in Sungai Durian Sub-District, Kotabaru Regency - Luthfia Amni Rismiyati; Farraz Reannisa; Syifa Nur Aghnia; Aslamiah Aslamiah; Celia Cinantya (International Journal Labs, 2025)
The quality of education in schools is influenced by various factors, including financial management, school climate, and teacher performance. These factors play a crucial role in improving school services and overall educational outcomes. This study was conducted to explore how these variables impact the quality of education in public junior high schools in the Sungai Durian subdistrict, Kotabaru Regency. The objective of this research was to determine the influence of financial management, school climate, and teacher performance on the quality of education in public junior high schools. A quantitative and explanatory research approach was used in this study. Data was collected through questionnaires distributed to respondents, including school administrators, teachers, and staff. The analysis employed multiple linear regression, with a T-test to examine the significance of the relationships between the variables. The study found that financial management, school climate, and teacher performance all have a positive relationship with school services and the quality of education. The T-test results showed that the values for financial management (4.343), school climate (3.426), and teacher performance (3.426) were higher than the T-table value, indicating significant positive influences. These findings suggest that improving financial management, enhancing the school climate, and increasing teacher performance are essential strategies for improving the quality of education in junior high schools. Educational authorities should focus on these areas to foster a more conducive learning environment and better educational outcomes.